The Implementation of the Penalty System Programme in Schools from the Perspectives of Teachers and Students - Md Nor, Sharifah; Arunasalam, Geetha (2008)
The Penalty System Programme (PSP) is used by some schools to control discipline problems amongst their students. There are two types of Penalty System implemented; Penalty System With Merit(PSM) and Penalty System Without Merit (PSWM).This paper aims to discuss the findings of a study pertaining to the effectiveness of both systems based on the perceptions of secondary school teachers and students.This case study employs both the qualitative and quantitative research approaches. Four schools in a school district, two each implementing the different systems were purposively sampled, involving 710 students and 171 teachers. Data were collected using questionnaires and interviews were also carried out on 20 teachers and 20 students.The T-test analysis shows that both teachers and students perceive PSP as mediocre. There is also no significant difference on the perception of teachers and students towards the effectiveness of both types of PSP.The Ttest however shows that there is a significant difference between teachers and students on the level of agreement regarding the effectiveness of the different types of PSP. More teachers agree on the usage of penalty points compared to students while more students agree on the usage of merit points compared to teachers. The qualitative data reveal that generally teachers and students find the implementation of PSP helpful in controlling disciplinary problems and to create conducive learning environment. Teachers however find the PSM as time consuming while students find it good, true to the purpose of PSP.Teachers are critical of the penalty points which penalize students for trivial offences. The findings of the study have implications on a more effective implementation of PSP in schools.